A critical review on graphene oxide membrane for industrial wastewater treatment - An, Ye-Chen; Gao, Xiao-Xu; Jiang, Wen-Li; Han, Jing-Long; Ye, Yuan; Chen, Tian-Ming; Ren, Rui-Yun; Zhang, Jia-Hui; Liang, Bin; Li, Zhi-Ling; Wang, Ai-Jie; Ren, Nan-Qi (Environmental research, 2023)
An important way to promote the environmental industry's goal of carbon reduction is to promote the recycling of resources. Membrane separation technology has unique advantages in resource recovery and advanced treatment of industrial wastewater. However, the great promise of traditional organic membrane is hampered by challenges associated with organic solvent tolerance, lack of oxidation resistance, and serious membrane fouling control. Moreover, the high concentrations of organic matter and inorganic salts in the membrane filtration concentrate also hinder the wider application of the membrane separation technology. The emerging cost-effective graphene oxide (GO)-based membrane with excellent resistance to organic solvents and oxidants, more hydrophilicity, lower membrane fouling, better separation performance has been expected to contribute more in industrial wastewater treatment. Herein, we provide comprehensive insights into the preparation and characteristic of GO membranes, as well as current research status and problems related to its future application in industrial wastewater treatment. Finally, concluding remarks and future perspectives have been deduced and recommended for the GO membrane separation technology application for industrial wastewater treatment, which leads to realizing sustainable wastewater recycling and a nearly “zero discharge” water treatment process. [Display omitted] •Detailed description of the demand for industrial wastewater advanced treatment.•The characteristics and performance of GO membrane in advanced treatment of industrial wastewater were described.•The innovative application of GO membrane in advanced treatment of industrial wastewater was summarized.•How to deal with membrane fouling of GO membrane in industrial wastewater treatment was discussed in detail.•The application potential of GO membrane in industrial wastewater treatment was prospected in detail.